A super strong, high toughness, corrosion resistant, weldable 7000 series aluminum alloy and its preparation method
By adding trace elements such as Er, Y, Sn to the Al-Zn-Mg aluminum alloy and using a three-stage homogenization heat treatment process to form a nanostructure with high thermal stability, the contradiction between the strength and plasticity of the existing aluminum alloy is solved, and aluminium alloy with high strength, high plasticity, high corrosion resistance and weldability is achieved, which is suitable for automotive structural parts and alloy profiles.
Patent Information
- Application Number
- CN202310282460.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-22
AI Technical Summary
While improving strength, the existing Al-Zn-Mg aluminum alloys are difficult to maintain high plasticity, corrosion resistance and welding, and the cost is high, which limits its industrial application.
By optimizing the composition of aluminum alloy, adding trace elements such as Er, Y, Sn, and using a three-stage homogenization heat treatment process, a high-thermal stability Al3Er/Al3Y/Al3Zr double-layer core-shell nanostructure is formed, which regulates fine grains and improves the strength, plasticity and corrosion resistance of the alloy.
It realizes the ultra-high strength, high plasticity, high corrosion resistance and welding properties of aluminum alloys. It is suitable for automotive structural parts and alloy profiles, reducing costs and promoting industrial applications.
Smart Images

Figure CN116287904B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and specifically relates to a super-strong, high-toughness, corrosion-resistant, weldable 7000 series aluminum alloy and a preparation method thereof. Background Art
[0002] 7xxx series aluminum alloys (i.e. Al-Zn-Mg series alloys) have become the preferred material for lightweighting of the new generation of automobiles due to their advantages such as high strength and high formability. Among them, 7003, 7005 and 7N01 alloys are widely used in the frame structure of new energy vehicles. However, the strength of the current Al-Zn-Mg series alloys is generally low. In order to improve the strength of Al-Zn-Mg series aluminum alloys, it is usually necessary to increase the content of Mg and Zn elements, but this will reduce the plasticity, corrosion resistance and forming properties of the alloy. Therefore, it is usually necessary to control the content of Zn and Mg elements to obtain suitable plasticity, corrosion resistance and forming properties. In addition, the strength of the alloy can also be increased by adding Cu elements to certain alloys, such as 7075 alloy, but this will reduce the welding performance of the alloy material.
[0003] Grain structure control is an important method to improve the plasticity and corrosion resistance of aluminum alloys. At present, Sc is the most effective rare earth element to inhibit the recrystallization of aluminum alloys. By obtaining non-recrystallized structure, the strength and stress corrosion resistance of the alloy can be improved, but the high cost limits the further industrial application of Sc-containing rare earth aluminum alloys. At the same time, although ultrafine-grained materials can be obtained by equal-channel angular extrusion (ECAP), the plasticity of the alloy is not effectively improved and it is not easy to industrialize. Therefore, if a new method can be developed to improve the strength, plasticity, corrosion resistance and weldability of the alloy, it will have a broad application prospect. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a novel composite rare earth alloy and a preparation method thereof, which improves the strength and corrosion resistance of the aluminum alloy, making it more suitable for use in automotive structural parts or alloy profiles.
[0005] To achieve the above object, the present invention is implemented by the following technical solutions:
[0006] A first aspect of the present invention provides an aluminum alloy, which includes, by weight percentage, 2.4-3.2% Mg, 4.6-5.5% Zn, 0.12-0.35% Cu, 0.15-0.35% Er, 0.15-0.35% Y, 0.10-0.20% Sn, 0.15-0.25% Zr and ≤0.5% Fe; the mass ratio of Zn to Mg is 1.5-1.65, and the mass ratio of Cu to Mg is 0.05-0.2.
[0007] As a preferred embodiment of the present invention, the aluminum alloy includes, by weight percentage, 2.8-3.0% Mg, 4.8-5.0% Zn, 0.20-0.25% Cu, 0.15-0.25% Er, 0.15-0.25% Y, 0.10-0.15% Sn, 0.20-0.25% Zr and ≤0.5% Fe; the mass ratio of Zn to Mg is 1.5-1.65, and the mass ratio of Cu to Mg is 0.05-0.2.
[0008] The present invention optimizes the design of the corrosion-resistant strengthening phase and, based on the rare earth / transition element composite microalloying principle, regulates the size and distribution of the dispersed second phase, thereby obtaining an aluminum alloy material with fine grains, thereby improving the strength, plasticity, corrosion resistance and weldability of the alloy.
[0009] Preferably, the content of impurity elements in the aluminum alloy is ≤0.15%. The impurity elements include but are not limited to Ti.
[0010] Preferably, the mass ratio of Er to Y is 0.8 to 1.2, and the mass ratio of Er to Zr is 1.3 to 1.8.
[0011] The second aspect of the present invention provides a method for preparing the aluminum alloy according to the first aspect, comprising the following steps:
[0012] S1. First melt the high-purity aluminum ingot at 725-745°C, then add Al-Cu50 and Al-Zr10 master alloys, and then add Mg, Al-Er5, Al-Y5 and Al-Sn5 after the master alloys are melted to obtain a completely molten metal solution;
[0013] S2, degassing the completely molten metal melt and then refining it at 730°C-750°C;
[0014] S3, after standing, cool the molten metal to 700°C-720°C, add Al-5wt%Ti-1wt%B grain refiner, and then cast it into alloy ingot;
[0015] S4. After the alloy ingot is subjected to three-stage homogenization heat treatment, it is subjected to hot rolling, solid solution treatment, quenching and aging treatment to obtain the aluminum alloy.
[0016] Preferably, the three-stage homogenization heat treatment is: firstly, the temperature is raised from room temperature to 250-350°C at a heating rate of 20-50°C / h, and kept at this temperature for 15-30h; then, the temperature is further raised to 400-450°C at a heating rate of 20-50°C / h, and kept at this temperature for 15-30h; then, the temperature is further raised to 460-490°C at a heating rate of 20-50°C / h, and kept at this temperature for 15-30h; finally, the temperature is lowered to below 100°C at a cooling rate of 20-50°C / h. By adopting the three-stage homogenization heat treatment process, the precipitation of the saturated matrix can be effectively promoted, the Al3 (Er, Y, Zr) phase of the highly dispersed rare earth / transition group composite elements can be formed, and the coarse grains can be suppressed.
[0017] Preferably, the aging treatment is carried out at a temperature of 180-190°C and for a time of 10-14 hours.
[0018] The present invention adds trace elements such as Er, Y, Sn, and adopts a three-stage homogenization heat treatment process to preferentially homogenize and diffuse the Y element, and then diffuse the Er element and the Zr element in sequence, precipitating to form a highly dispersed Al3Er / Al3Y / Al3Zr double-layer core-shell nanostructure; and through the segregation of the Sn trace element at the Al3Er / Al3Y / Al3Zr double-layer core-shell interface, the structural thermal stability of the core-shell interface is improved, and the recrystallization process of the alloy is inhibited. At the same time, based on the alloying principle, the alloy composition of the aluminum alloy is optimized and designed, that is, by controlling the mass ratio of Zn to Mg to 1.5-1.65 and the mass ratio of Cu to Mg to 0.05-0.2, a high-strength and corrosion-resistant T phase structure is obtained to avoid the formation of a η phase with poor corrosion resistance, and by adding a trace amount of Cu element, the electrode potential of the T phase is increased, and the corrosion resistance of the alloy is further improved. Through the above improvements, the present invention can ultimately obtain ultra-high strength, high corrosion resistance, weldable aluminum alloy, which is expected to be used in automotive structural parts or in alloy profiles.
[0019] Preferably, the hot rolling start temperature is 430-450°C, the pass reduction is 4%-32%, the total hot rolling deformation is greater than 92%, and the final rolling temperature is lower than 320°C.
[0020] Preferably, the solution treatment is carried out at 460-470°C for 1-2h, with a heating rate greater than 120°C / min.
[0021] The third aspect of the present invention provides use of the aluminum alloy described in the first aspect in preparing automotive structural parts and / or alloy profiles.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention discloses a super strong, high toughness, corrosion resistant weldable 7000 series aluminum alloy, which comprises 2.4-3.2% Mg, 4.6-5.5% Zn, 0.12-0.35% Cu, 0.15-0.35% Er, 0.15-0.35% Y, 0.10-0.20% Sn, and 0.15-0.25% Zr by weight percentage. The invention obtains a high-strength, corrosion-resistant T phase structure by controlling the mass ratio of Zn to Mg to be 1.5-1.65 and the mass ratio of Cu to Mg to be 0.05-0.2, avoids the formation of an η phase with poor corrosion resistance, and further improves the corrosion resistance of the alloy by adding a trace amount of Cu element to increase the electrode potential of the T phase. At the same time, by adding Er, Y, Sn, and Zr elements, and adopting a three-stage homogenization heat treatment process to prepare an aluminum alloy, wherein the Y element is first homogenized and diffused, and then the Er element and the Zr element are diffused in sequence, and precipitated to form a highly dispersed Al3Er / Al3Y / Al3Zr double-layer core-shell nanostructure; at the same time, through the segregation of the Sn trace element at the Al3Er / Al3Y / Al3Zr double-layer core-shell interface, the thermal stability of the core-shell interface structure is improved, and the alloy recrystallization process is inhibited. Therefore, an aluminum alloy with ultra-high strength, high plasticity, and high corrosion resistance can be obtained by the method of the present invention, and the aluminum alloy obtained by the present invention is suitable for use in automotive structural parts or in its profiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The microstructure diagram of the aluminum alloy obtained in Example 1;
[0025] Figure 2 This is the microstructure diagram of the aluminum alloy obtained in Comparative Example 4. DETAILED DESCRIPTION
[0026] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0028] Preparation methods of 7000 series aluminum alloys of Examples 1-2 and Comparative Examples 1-4
[0029] The composition of each aluminum alloy is shown in Table 1. The preparation of the aluminum alloy includes the following steps:
[0030] (1) At a temperature of 735°C, 99.99% high-purity aluminum ingots are first melted, and then Al-Cu50 and Al-Zr10 intermediate alloys are added. After the intermediate alloys are melted, 99.99% (purity) magnesium, Al-Er5, Al-Y5, and Al-Sn5 are added to obtain a completely molten metal melt.
[0031] (2) adding 1.5 wt% hexachloroethane to the completely molten metal melt for degassing, stirring the mixture thoroughly, and then refining the mixture. During the refining, the temperature of the metal is maintained at 740° C. for 2 hours.
[0032] (3) The temperature of the molten metal is lowered to 720°C, an Al-5wt%Ti-1wt%B grain refiner is added, and the mixture is stirred appropriately. After standing for 30 minutes, the molten metal is poured into a metal mold at a temperature of 250°C, and an alloy ingot is obtained after the temperature is lowered to room temperature.
[0033] (4) Three-stage homogenization heat treatment: first, the alloy ingot is heated from room temperature to 300°C at a heating rate of 30°C / h and kept at this temperature for 16 hours; then, the temperature is further heated to 425°C at a heating rate of 30°C / h and kept at this temperature for 24 hours; then, the temperature is further heated to 470°C at a heating rate of 50°C / h and kept at this temperature for 16 hours; finally, the temperature is cooled to below 100°C at a cooling rate of 50°C / h.
[0034] (5) hot rolling the alloy ingot: the starting rolling temperature is 435° C., the pass reduction is 4% to 32%, the total hot rolling deformation is greater than 92%, and the final rolling temperature is lower than 320° C. to obtain a hot-rolled plate;
[0035] (6) Solution treatment: The hot-rolled plate was placed in a heat treatment furnace at 470°C for 1 h for solution treatment, with the sample heating rate being greater than 10°C / min to obtain an alloy sample;
[0036] (7) Quenching treatment: The alloy sample after solution treatment is transferred from the solution treatment temperature to room temperature water for quenching treatment.
[0037] (8) Aging treatment: The alloy sample after quenching is placed at 185°C for 12 hours for aging treatment to obtain an aluminum alloy.
[0038] Table 1 Composition and weight percentage (%) of aluminum alloys of Examples 1-2 (ingot numbers correspond to 1#-2# respectively) and Comparative Examples 1-4 (ingot numbers correspond to 3#-6# respectively)
[0039]
[0040] Comparative Example 5 Preparation method of 7000 series aluminum alloy
[0041] Comparative Example 5 is Sample 7#, which is different from Sample 1# in that: Step (4) of Comparative Example 5 does not adopt a three-stage homogenization process, but adopts a conventional single-stage homogenization heat treatment method, and the other processes are the same. The conventional single-stage homogenization heat treatment process is: heating the obtained alloy ingot from room temperature to 470°C at a heating rate of 50°C / h, keeping the temperature for 24h; finally cooling the temperature to below 100°C at a cooling rate of 50°C / h, and obtaining an alloy ingot.
[0042] Comparative Example 6 Preparation Method of 7000 Series Aluminum Alloy
[0043] Comparative Example 6 is Sample 8#, which is different from Sample 1# in that the conventional aging process is used in step (8) of Comparative Example 6, and the other processes are the same. The conventional aging process is to place the alloy sample after quenching at 120°C for 24 hours for aging treatment.
[0044] Experimental Example 1 Performance Test of 7000 Series Aluminum Alloy
[0045] The aluminum alloy plates prepared in Examples 1-2 and Comparative Examples 1-6 were respectively subjected to mechanical, corrosion and weldability tests according to national standards GB / T228.1, GB / T 15970.6 and GB / T 2651. The test results are shown in Table 2 below.
[0046] As can be seen from Table 2, the tensile strength of the aluminum alloy products obtained by Examples 1-2 exceeds 570MPa, the elongation exceeds 13.8%, the stress corrosion cracking time reaches more than 93, the mechanical properties and corrosion resistance meet the requirements of automotive structural aluminum alloys, and have broad application prospects. It can be clearly seen from Comparative Example 1 that Comparative Example 1 is high Zn / Mg, forming a η phase with poor corrosion resistance, and the time for stress corrosion cracking to appear is the shortest; it is easy to produce welding cracks and has the lowest welding coefficient. No trace Cu element is added in Comparative Example 2. Compared with Examples 1 and 2, the time for stress corrosion cracking to appear is reduced, and the strength is reduced. Comparative Examples 3 and 4 do not add Y elements and Sn elements. Since the Al3Er / Al3Y / Al3Zr double-layer core-shell nanostructure with high thermal stability is not formed, the grain size of the alloy cannot be effectively refined, the time for stress corrosion to appear is significantly reduced, and the effect of inhibiting welding cracks is reduced, and the welding coefficient is reduced, which does not meet the requirements of automotive structural aluminum alloys.
[0047] at the same time, Figure 1 is the microstructure diagram of the aluminum alloy obtained in Example 1; Figure 1It can be seen that after the three-stage homogenization treatment, the aluminum alloy of Example 1 forms a highly thermally stable Al3Er / Al3Y / Al3Zr double-layer core-shell nanostructure, which significantly inhibits the recrystallization process of the alloy and obtains a non-recrystallized small-angle grain boundary structure, thereby effectively improving the alloy's stress corrosion resistance. Figure 2 is the microstructure diagram of the aluminum alloy obtained in Comparative Example 4; Figure 2 It can be seen that the aluminum alloy of Comparative Example 4, due to the lack of addition of trace Sn elements, failed to effectively inhibit the recrystallization process of the alloy after the three-stage homogenization treatment, and obtained a recrystallized large-angle grain boundary structure, and the alloy's stress corrosion resistance was reduced.
[0048] In addition, it can be seen from Table 3 that the 7# aluminum alloy obtained in Comparative Example 5, because the conventional homogenization heat treatment method is adopted instead of the three-stage homogenization heat treatment, the tensile strength of the obtained aluminum alloy is only 565MPa, and the stress corrosion resistance and welding coefficient are lower than the aluminum alloy obtained in Example 1 treated by the three-stage homogenization process, and cannot meet the requirements of the automotive structure field. It can be seen from Table 4 that the 8# aluminum alloy obtained in Comparative Example 6, because the conventional 7 series alloy T6 heat treatment method is adopted instead of the new aging process, a high content of T phase is not obtained, and the tensile strength of the obtained aluminum alloy is only 465MPa, and the performance is far lower than that of the aluminum alloy obtained in Example 1, and cannot meet the requirements of the automotive structure field.
[0049] Table 2 Mechanical, corrosion and weldability test results of aluminum alloys of Examples 1-2 and Comparative Examples 1-4
[0050]
[0051] Table 3 Mechanical, corrosion and weldability test results of aluminum alloys obtained in Example 1 and Comparative Example 5
[0052]
[0053] Table 4 Mechanical, corrosion and weldability test results of aluminum alloys of Example 1 and Comparative Example 6
[0054]
[0055] In summary, the present invention adds trace elements such as Er, Y, Sn, and adopts a three-stage homogenization heat treatment process to preferentially homogenize and diffuse the Y element, and then diffuse the Er element and the Zr element in sequence, precipitating to form a highly dispersed Al3Er / Al3Y / Al3Zr double-layer core-shell nanostructure; and through the segregation of the Sn trace element at the Al3Er / Al3Y / Al3Zr double-layer core-shell interface, the structural thermal stability of the core-shell interface is improved, and the recrystallization process of the alloy is inhibited. At the same time, based on the alloying principle, the alloy composition of the aluminum alloy is optimized and designed, that is, by controlling the mass ratio of Zn to Mg to 1.5-1.65 and the mass ratio of Cu to Mg to 0.05-0.2, a high-strength and corrosion-resistant T phase structure is obtained to avoid the formation of a η phase with poor corrosion resistance, and by adding a trace amount of Cu element, the electrode potential of the T phase is increased, and the corrosion resistance of the alloy is further improved, and finally an ultra-high-strength, high-corrosion-resistant, weldable aluminum alloy suitable for automotive structural parts or alloy profiles is obtained.
[0056] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. An aluminum alloy, characterized in that: The aluminum alloy comprises, by weight percentage, 3.0% Mg, 5.0% Zn, 0.20% Cu, 0.25% Er, 0.20% Y, 0.20% Sn, 0.20% Zr and the balance Al; the preparation method of the aluminum alloy comprises the following steps: S1, at 725 The high purity aluminum ingot is first melted at 745℃, and then Al Cu50、Al Zr10 master alloy, add Mg and Al after the master alloy is melted Er5、Al Y5, Al Sn5, to obtain a completely molten metal solution; S2: After degassing the completely molten metal, heat it at 730℃ Refining at 750°C; S3, after standing, cool the molten metal to 700℃ 720℃, then add Al 5wt%Ti 1wt% B grain refiner, which is then cast into an alloy ingot; S4. After the alloy ingot is subjected to a three-stage homogenization heat treatment, it is subjected to hot rolling, solution treatment, quenching and aging treatment to obtain an aluminum alloy; the three-stage homogenization heat treatment is as follows: first, the obtained alloy ingot is heated from room temperature to 300°C at a heating rate of 30°C / h, and kept warm for 16 hours; then, the temperature is continuously increased to 425°C at a heating rate of 30°C / h, and kept warm for 24 hours; then, the temperature is continuously increased to 470°C at a heating rate of 50°C / h, and kept warm for 16 hours; finally, the temperature is reduced to below 100°C at a cooling rate of 50°C / h.
2. The aluminum alloy according to claim 1, characterized in that The content of impurity elements in the aluminum alloy is ≤0.15%.
3. The aluminum alloy according to claim 1, characterized in that The aging treatment temperature is 180-190°C and the time is 10 14h.
4. The aluminum alloy according to claim 1, characterized in that The hot rolling start temperature is 430-450°C, the pass reduction is 4%-32%, the total hot rolling deformation is greater than 92%, and the final rolling temperature is lower than 320°C.
5. The aluminum alloy according to claim 1, characterized in that The solution treatment is carried out at 460-470° C. for 1-2 hours, with a heating rate greater than 120° C. / min.
6. A method as claimed in claim 1 5. Use of the aluminum alloy described in any one of items 5 in the preparation of automobile structural parts and / or alloy profiles.
Citation Information
Patent Citations
Corrosion-resistant structural aluminum alloy and preparation method thereof
CN107447150A